On Being Between: Apocalypse, Adaptation, McCarthy - Stacey Peebles (European Journal of American Studies)
Cormac McCarthy’s career-long interest in ideas of apocalypse is most evident in his 2006 novel The Road, which was then adapted for film by John Hillcoat in 2009. Apocalypse can be understood as a liminal state, existing in between the old and new worlds, a similar kind of space to that inhabited by film adaptations, which are situated both in relation to their source text and also as new artworks. McCarthy’s novel and Hillcoat’s film each incorporate the popular conception of apocalypse as disaster as well as the theological understanding of it as the revelation of previously hidden mysteries. The film, however, inhabits that apocalyptic and adaptive liminality uncomfortably, approaching the novel with a reverence that ultimately fails to productively superimpose Hillcoat’s vision with McCarthy’s.